ANALISIS STRATEGI PENGUMPULAN ZAKAT, INFAQ, DAN SHADAQAH PADA MASA PANDEMI COVID-19: STUDI PADA LAZ ZAKAT SUKSES - Ibrahim (2022)
LAZ Zakat Sukses Depok City is an Amil Zakat institution that focuses on Dhu'afa community empowerment programs. In the collection of zakat, infaq, and Shadaqah, LAZ Zakat Sukses Depok City certainly has a different collection strategy from other zakat institutions, especially with the Covid-19 pandemic. That way this study aims to analyze the opportunities, challenges and strategies for collecting zakat, infaq, and shadaqah during the Covid-19 pandemic. The research method used in this study is a descriptive qualitative research method with a case study approach. With the case study approach, researchers must get primary data by going directly to the object, namely LAZ Zakat Sukses Depok City. The data taken is in the form of interviews with Amil in this case the management of LAZ Zakat Sukses Depok City, while other data is taken from the LAZ Zakat Sukses document of Depok City related to the collection of zakat, infaq, and Shadaqah. Data validity techniques use triangulation methods from various sources and methods, and data analysis techniques are carried out with SWOT analysis. The results of this study show that LAZ Zakat Success in collecting ZIS during the Covid-19 pandemic has strengths and weaknesses, namely zakat friends who are widespread throughout depok and large technological costs, then opportunities and challenges including increased public awareness and the demands of adapting to technology.